Does small-sided games training improve physical fitness and team-sport-specific skills? A systematic review and meta-analysis - Hammami, A.; Gabbett, T. J.; Slimani, M.; Bouhlel, E. (The Journal of Sports Medicine and Physical Fitness, 2018)
INTRODUCTION: This paper aimed to systematically review the training effects of small-sided games (SSG) on physical fitness and specific skills related to team sport according to the level of play and the period of the season. EVIDENCE ACQUISITION: The search covered the following electronic databases (PubMed, Google Scholar, and ScienceDirect). The publications` search period ranged from 2000 to 2016. The terms (small-sided game, training, skill-based game, aerobic fitness, sprint, agility, jump and team sports) were used either singularly or combined in a systematic sequence. Appraisal of 16 articles (15 were analyzed) was performed after the application of exclusion criteria and quality assurance processes and the standardized mean effects were measured using random effects. EVIDENCE SYNTHESIS: The results revealed that SSG training had a large beneficial effect on maximal oxygen uptake V?O2max (effect size 1.94; 95% CI: 0.15, 3.74; I2=94%), agility (-1.49; 95% CI: -2.27, -0.71; I2=80%), and repeated sprint ability (-1.19; 95% CI: -2.17, -0.21; I2= 53%). There was a moderate beneficial effect on 10- and 20-m sprint performance (-0.89; 95% CI: -1.7, -0.07; I2=88%), jump height (0.68; 95% CI: 0.03, 1.33; I2= 79%), and intermittent endurance (0.61; 95% CI: 0.17, 1.05; I2= 0%). The results also showed greater positive effects on specific skills (specific endurance and agility tests and techniques) after SSG when compared with generic or agility training. CONCLUSIONS: Small-sided games may represent an effective strategy of multicomponent training that can induce greater positive effects on specific skills tasks when compared with interval or agility training and moderate to large improvements in team sport-related physical fitness.